Impact of ⟨3D⟩ non-local thermodynamic equilibrium on the galactic chemical evolution of oxygen with the radial velocity experiment - Guiglion, Guillaume (Astronomy and astrophysics, 2025)
Methods. Using the standard spectral fitting method, we determined for the first time the LTE and NLTE abundances of oxygen from the O I triplet at 8446 Å in turn-off and dwarf stars, based on intermediate-resolution RAVE spectra and assuming both 1D and ⟨3D⟩ model atmospheres. - Results. We find that NLTE effects play a significant role when determining oxygen even at a resolution of R = 7500. Typical NLTELTE corrections of the order of -0.12 dex are measured in dwarfs and turn-off stars using 1D MARCS models. In addition, ⟨3D⟩ modelling significantly impacts the oxygen abundance measurements. In contrast to applying ⟨3D⟩ NLTE abundance corrections or the classical 1D LTE, the full ⟨3D⟩ NLTE spectral fitting improves abundance precision by nearly 10%. We also show that the decrease in [O/Fe] in the super-solar metallicity regime is characterised by a flat trend when computed in ⟨3D⟩ NLTE from a full spectral fitting. We attribute this flattening at super-solar [Fe/H] to the interplay between locally born stars with negative [O/Fe] and stars that migrate from the inner MW regions with super-solar [O/Fe], supporting the complex chemo-dynamical history of the Solar neighbourhood. - Conclusions. Our results are key for understanding the effects of ⟨3D⟩ and NLTE when measuring oxygen abundances in intermediateresolution spectra. NLTE effect should be taken into account when confronting Galactic chemical evolution models with observations. This work is a test bed for the spectral analysis of the 4MOST low-resolution spectra that share similar properties as the RAVE spectra in the red wavelength domain.
Gesehen am 24.11.2025